2010
DOI: 10.1063/1.3382341
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium adiabatic molecular dynamics simulations of methane clathrate hydrate decomposition

Abstract: Nonequilibrium, constant energy, constant volume (NVE) molecular dynamics simulations are used to study the decomposition of methane clathrate hydrate in contact with water. Under adiabatic conditions, the rate of methane clathrate decomposition is affected by heat and mass transfer arising from the breakup of the clathrate hydrate framework and release of the methane gas at the solid-liquid interface and diffusion of methane through water. We observe that temperature gradients are established between the clat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 41 publications
6
101
0
Order By: Relevance
“…Figure shows the time dependence of pressure in the simulation system; it can be seen that the variation of pressure might not be negligible. However, the tendency is extremely similar to the pressure curves simulated by Alavi and Ripmeester at the initial temperature of 310 K under the initial pressure of 10 MPa . In Figure , the pressure of the system increases gradually with the escape of methane gas.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Figure shows the time dependence of pressure in the simulation system; it can be seen that the variation of pressure might not be negligible. However, the tendency is extremely similar to the pressure curves simulated by Alavi and Ripmeester at the initial temperature of 310 K under the initial pressure of 10 MPa . In Figure , the pressure of the system increases gradually with the escape of methane gas.…”
Section: Resultssupporting
confidence: 77%
“…The hydrate absorbs heat supplied by water. Due to the nonequilibrium characteristic of decomposition, there appears a temperature drop in the whole system . And decomposition no longer continues when the temperature reaches the equilibrium temperature of the system .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accurate knowledge of the thermodynamic and kinetic properties of methane hydrate is a primary goal for a number of studies. MD studies considering methane hydrates have been reported as early as 1983 with the pioneering work of Tse et al 44 Subsequently, a significant number of MD studies examining methane hydrates have been reported focusing on topics such as hydrate nucleation, [45][46][47][48][49][50] formation and growth, 51,52 dissociation, [53][54][55][56][57][58] inhibition, 59-61 heat transfer effects, 62-64 the effect of hydrate contact with solid surfaces, 65-68 methane replacement by carbon dioxide, [69][70][71][72] and the calculation of transport properties such as thermal conductivity, [73][74][75] or thermodynamic properties such as three-phase equilibrium conditions. [76][77][78][79] In the area of calculation of the three-phase equilibrium conditions for pure methane hydrate which is the main focus of the current study, there is a number of molecular simulation studies that have provided important insights of the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation of hydrates is usually simulated with the hydrate phase either in contact with liquid water along two parallel planes or in some cases with these phases surrounded by a silica phase to mimic the hydrate decomposition in natural deposits. [19][20][21][22][23][24][25][26][27][28] It has been observed that during methane hydrate decomposition, the guest methane molecules are released into the liquid water phase and form methane-rich regions. [29][30][31][32][33][34] It was also recently reported that formation of methane bubbles reduces the dissolved methane concentration in water thus increasing the dissociation rate of the solid hydrate.…”
Section: Introductionmentioning
confidence: 99%